Effect of electrode gap on the sensing properties of multiwalled carbon nanotubes based gas sensor - Saheed, M.S.M. (American Institute of Physics Inc., 2016)
Vertically aligned multiwalled carbon nanotubes (MWCNT) were grown on Si substrate coated with alumina and iron using chemical vapor deposition. Electrode gap of 10, 25 and 50 Î¼m were adopted to determine the effect of varying gap spacing on the sensing properties such as voltage breakdown, sensitivity and selectivity for three gases namely argon, carbon dioxide and ammonia. Argon has the lowest voltage breakdown for every electrode gap. The fabricated MWCNT based gas sensor drastically reduced the voltage breakdown by 89.5 when the electrode spacing is reduced from 50 Î¼m to 10 Î¼m. The reduction is attributed to the high non-uniform electric field between the electrodes caused by the protrusion of nanotips. The sensor shows good sensitivity and selectivity with the ability to detect the gas in the mixture with air provided that the concentration is â¥ 20 where the voltage breakdown will be close to the pure gas. Â© 2016 Author(s).